Effects of Different Types of Agricultural Land Use on the Occurrence of Common Aquatic Bugs (Nepomorpha, Heteroptera) in Habitats with Slow Flowing Water in Bulgaria, Southeast Europe - Desislava Stoianova (Diversity, 2023)
Agricultural activities can have a significant impact on aquatic organisms, including aquatic insects. Most of the aquatic Heteroptera are known as moderately tolerant to low oxygen and high nutrient concentrations. Nevertheless, the complex effects of agriculture (source of both pesticides and nutrient loads) on this group are still unclear. Therefore, the relationship between six agricultural land use classes and the occurrence of common aquatic bugs in Bulgaria was studied. In order to avoid detection bias, presence-only models were applied; Maxent algorithm was used. According to the results, land use practices connected to arable land (annual crops) have stronger influence on the occurrence of the selected aquatic Heteroptera species than those connected to perennial crops (vineyards and fruit trees). Higher sensitivity to the effects of agriculture was indicated for species preferring microhabitats without macrophyte vegetation, Aphelocheirus aestivalis (Fabricius, 1794) and Micronecta griseola Horváth, 1899, compared to species preferring macrophyte dominated sites, Nepa cinerea Linnaeus, 1758, Ilyocoris cimicoides (Linnaeus, 1758) and Sigara striata (Linnaeus, 1758).